Animal model contributes to the development of intracranial aneurysm: A bibliometric analysis - Chen, Jia; Liu, Jing; Liu, Xin; Zeng, Chudai; Chen, Zhou; Li, Shifu; Zhang, Qian (Frontiers in Veterinary Science, 2022)
Introduction Studies on intracranial aneurysms (IAs) using animal models have evolved for decades. This study aimed to analyze major contributors and trends in IA-related animal research using bibliometric analysis. Methods IA-related animal studies were retrieved from the Web of Science database. Microsoft Excel 2010, GraphPad Prism 6, VOSviewer, and CiteSpace were used to collect and analyze the characteristics of this field. Results A total of 273 publications were retrieved. All publications were published between 1976 and 2021, and the peak publication year is 2019. Rat model were used in most of the publications, followed by mice and rabbits. Japan (35.5%), the United States (30.0%), and China (20.1%) were the top three most prolific countries. Although China ranks third in the number of publications, it still lacks high-quality articles and influential institutions. Stroke was the most prolific journal that accepted publications related to IA research using animal models. Circulation has the highest impact factor with IA-related animal studies. Hashimoto N contributed the largest number of articles. Meng hui journal published the first and second highest cited publications. The keywords “subarachnoid hemorrhage,” “macrophage,” “rupture,” “mice,” “elastase,” “gene,” “protein,” “proliferation,” and “risk factors” might be a new trend for studying IA-related animal research. Conclusions Japan and the Unites States contributed the most to IA–related animal studies, in terms of both researchers and institutions. Although China ranks third in terms of the number of publications, it should strengthen the quality of its publications. Researchers should pay attention to the latest progress of Stroke, Journal of Neurosurgery, Neurosurgery, and Circulation for their high-quality IA-related animal studies. Using animal IA models, especially mice, to investigate the molecular mechanisms of IA may be the frontier topic now and in future.